Dilematika Posisi Perempuan Sebagai Ibu dalam Tindak Pidana Pembuangan dan Pembunuhan Bayi Tinjauan Viktimologi Kritis - Laili Nur Anisah; Bella Setia Ningrum Amin (DOKTRINA: JOURNAL OF LAW, 2022)
The issue of the disposal and infanticide by their biological mothers is not one of the reasons for the abolition of the crime. Mothers can still be prosecuted as criminals. Nevertheless, that is not the only problem. The reason for fear of the birth of their baby is known by many people needs to be re-examined. This paper attempts to look at the role of mothers as perpetrators of the crime of disposal and infanticide through the perspective of critical victimology. The study was conducted with a comparative study of 5 district court rulings on infanticide and infant discharge. The results of this study indicate that the intense pressure comes from the mother's fear of growing and developing values in society about unwanted pregnancies. This fear encourages mothers to have independent births that can kill themselves and their babies. Another result of the study is that the mother's partner has never been charged with participating in or assisting in infanticide.